Exploring students' misunderstandings of graphics generated by mathematics assistant - Blanco Sánchez, Ramón; Báez Ureña, Neel Lobatchewski; García Rosario, Reinaldo (Transformación, 2021)
Objective: The paper aims at exploring students' misunderstandings of graphics generated by mathematics assistant, and to provide some orientations in order to avoid them.Methods: The author rely on exploring students’ misunderstanding of graphics generated by mathematics assistants in the solving mathematics homework as compared to results described in the bibliography. A questionnaire conformed by eight tasks containing graphics, in which interpretation the students usually have difficulties was given to 30 engineer students from the Autonomous University of Santo Domingo. The answers were evaluated by qualitative and quantitative methods.Results: The findings show that student's difficulties in interpreting unusual results coincidence with those described in the literature.Conclusions: The need of training the students in using mathematics knowledge in order to interpret correctly graphics displayed on the screen described in the literature coincides with the findings of this research. Likewise, the authors arrived at the conclusion that the students need to be capable of managing screen dimensions according to the data they are working with
Keywords: Mathematics instruction; didactics; mathematical concepts; educational software